2013
DOI: 10.1002/adhm.201200465
|View full text |Cite
|
Sign up to set email alerts
|

Unique Antimicrobial Effects of Platelet‐Rich Plasma and Its Efficacy as a Prophylaxis to Prevent Implant‐Associated Spinal Infection

Abstract: Platelet-rich-plasma (PRP) has attracted great attention and has been increasingly used for a variety of clinical applications including orthopaedic surgeries, periodontal and oral surgeries, maxillofacial surgeries, plastic surgeries, and sports medicine. However, very little is known about the antimicrobial activities of PRP. In this study, PRP is found to have antimicrobial properties both in vitro and in vivo. In vitro, the antimicrobial properties of PRP have been found to be bacterial strain specific and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 56 publications
0
50
1
Order By: Relevance
“…In contrary to Li et al (2013) study, PPP has demonstrated antimicrobial effect. However, a greater susceptibility for activated PRP was observed.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In contrary to Li et al (2013) study, PPP has demonstrated antimicrobial effect. However, a greater susceptibility for activated PRP was observed.…”
Section: Discussioncontrasting
confidence: 67%
“…The reasons for the inconsistency between their results and the results of the current study may be explained by differences in the bacterial isolates and the increased frequency of antimicrobial use in mi nor surgical procedures which may lead to increased antimicrobial resistance in our population. Additionally, in the current study, CaCl2, which may have a weaker and more prolonged activation time, has been used for activation instead of thrombin (Li et al, 2013). Moreover, the different protocol used for PRP preparation can lead to products with different cellular components and biological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts were then collected by centrifugation at 1200 rpm at 4°C for 7 min, and the pellet was washed twice with PBS. Slides were then prepared as previously reported [[63]]. In brief, osteoblasts were fixed with 2% paraformaldehyde and 4% glutaraldehyde mixed with 0.075 M PBS for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The antimicrobial action of PRP involves human beta defensin‐3, which is released in bactericidal concentrations, and to functionally active complement . The antimicrobial activity of PRP is influenced by how the fibrin sealant and thrombin are prepared, and on the concentration of thrombin used . However, it must be noted that the application of thrombin alone to skin flaps increases their necrosis …”
Section: Newer Treatments For Pressure Ulcersmentioning
confidence: 99%
“…64 The antimicrobial activity of PRP is influenced by how the fibrin sealant 65 and thrombin are prepared, 66 and on the concentration of thrombin used. 67 However, it must be noted that the application of thrombin alone to skin flaps increases their necrosis. 68 PRP promotes tissue granulation, synthesis of extracellular matrix, tissue formation, and the inflammatory phase of the wound healing process in healthy and healing-impaired animal models and clinical trials.…”
Section: Electrical Stimulationmentioning
confidence: 99%